2022
DOI: 10.3389/fimmu.2022.909816
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Coregulatory Complexes in Tregs as Targets to Promote Anticancer Immune Responses

Abstract: T-regulatory (Treg) cells display considerable heterogeneity in their responses to various cancers. The functional differences among this cell type are heavily influenced by multiprotein nuclear complexes that control their gene expression. Many such complexes act mechanistically by altering epigenetic profiles of genes important to Treg function, including the forkhead P3 (Foxp3) transcription factor. Complexes that form with certain members of the histone/protein deacetylase (HDAC) class of enzymes, like HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…22 Tregs, a subpopulation of helper T cells, suppress the activation of immune cell types (such as CD4 T cells and CD8 T cells), limit immune responses, and maintain immune self-tolerance. 23 In our study, the CIBERSORTx tool, and ssGSEA algorithm found that B cells, CD8 T cells, NK cells, and TIL were more abundant in GPRASP1 high subgroup. Correlation analysis further revealed that GPRASP1 expression was significantly positively associated with B cells, CD4 T cells, CD8 T cells, and TIL, whereas significantly negatively correlated with Tregs.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…22 Tregs, a subpopulation of helper T cells, suppress the activation of immune cell types (such as CD4 T cells and CD8 T cells), limit immune responses, and maintain immune self-tolerance. 23 In our study, the CIBERSORTx tool, and ssGSEA algorithm found that B cells, CD8 T cells, NK cells, and TIL were more abundant in GPRASP1 high subgroup. Correlation analysis further revealed that GPRASP1 expression was significantly positively associated with B cells, CD4 T cells, CD8 T cells, and TIL, whereas significantly negatively correlated with Tregs.…”
Section: Discussionmentioning
confidence: 48%
“…TIL, refers to lymphocytes surrounding the tumor, represents the ability of tumor‐related immune responses, and can predict the therapeutic effect of immunotherapy 22 . Tregs, a subpopulation of helper T cells, suppress the activation of immune cell types (such as CD4 T cells and CD8 T cells), limit immune responses, and maintain immune self‐tolerance 23 . In our study, the CIBERSORTx tool, and ssGSEA algorithm found that B cells, CD8 T cells, NK cells, and TIL were more abundant in GPRASP1 high subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, although the non-Tax-target gene FOXP3 also significantly increased upon HDACi treatment, expression of FOXP3 remained ca. two logarithmic orders lower than expression of the target genes ( Supplementary Figure S3B , lower panel ( 54 )). These findings on the transcriptional level in MT-2 cells ( Figure 4C, D ; Supplementary Figure S3B ) paralleled the results from the transiently transfected Jurkat T-cells ( Figure 3C, D ; Supplementary Figure S2B ).…”
Section: Resultsmentioning
confidence: 99%